Hands-On Data Science with SQL Server 2017 Perform end-to-end data analysis to gain efficient data insight - Chmel, Marek (Packt Publishing Limited, 2018)
bFind, explore, and extract big data to transform into actionable insights /b h4Key Features/h4 ulliPerform end-to-end data analysis- from exploration to visualization /li liReal-world examples, tasks, and interview queries to be a proficient data scientist /li liUnderstand how SQL is used for big data processing using HiveQL and SparkSQL /li /ul h4Book Description/h4 SQL Server is a relational database management system that enables you to cover end-to-end data science processes using various inbuilt services and features. Hands-On Data Science with SQL Server 2017 starts with an overview of data science with SQL to understand the core tasks in data science. You will learn intermediate-to-advanced level concepts to perform analytical tasks on data using SQL Server. The book has a unique approach, covering best practices, tasks, and challenges to test your abilities at the end of each chapter.